Detection of neural action potentials using optical coherence tomography: intensity and phase measurements with and without dyes - Akkin, Taner; Landowne, David; Sivaprakasam, Aarthi (Frontiers in Neuroenergetics, 2010)
We review the use of optical coherence tomography (OCT) for detection of neural activity, and present a new approach for depth localization of neural action potentials using voltage sensitive dyes as contrast agents in OCT. A stained squid giant axon is imaged by spectral domain OCT. Changes in the intensity and phase of back-scattered light coming from regions around the membrane are measured during action potential propagation. The depth-resolved change in back-scattered intensity coincides with the arrival of action potential at the measurement area, and is synchronous with the changes in transmitted light intensity and reflection mode cross-polarized light intensity measured independently. The system also provides depth-resolved phase changes as an additional indication of activity. With further investigation our results could open a new era in functional imaging technology to localize neural activity at different depths in situ.